Prevention practices of vaginitis among Malaysian women and its associated factors - Wan Muda, Wan Mahfuzah; Wong, Li Ping; Tay, Sun Tee (Taylor & Francis, 2018)
Information on vaginal-related issues among Malaysian women is very limited. This study aimed to explore factors associated with preventive practices of vaginitis among Malaysian women. A cross-sectional computer-assisted telephone interview survey of a representative sample of multi-racial Malaysian women aged 18–50 years old was conducted from January to April 2014. Women from 1446 households responded to the survey and nearly one-third (32.1%) reported to have experienced vaginitis. In multivariate analyses, respondents in the urban locality were more likely to practice vaginitis prevention (OR = 1.40, 95% CI = 1.06–1.84) compared with those in the rural areas. Respondents who perceived low susceptibility to vaginitis were less likely to practice vaginitis prevention (OR = 0.72, 95% CI = 0.57–0.91) compared with responders who highly perceive susceptibility. Respondents who had no formal education were less likely to practice vaginitis prevention (OR = 0.16, 95% CI = 0.05–0.48) compared with those with tertiary education. This study showed that comprehensive education and health programmes need to focus on women with a low educational level, living in rural areas and women with low perceived susceptibility to vaginitis.Impact statementWhat is already known on this subject? Little is known about vaginitis issues among women in Malaysia. This study provides information regarding vaginitis among Malaysian women by looking at the factors associated with prevention practices. What do the results of this study add? From our study, factors associated with prevention practices were found to be educational level, locality, and perceived susceptibility of vaginitis. Those who perform fewer vaginitis prevention practices were women with a low educational level and those who live in rural areas. From the Health Belief Model, women with a low perceived susceptibility of vaginitis were less likely to carry out vaginitis prevention practices. What are the implications of these findings for clinical practice and/or further research? The findings may provide additional insights for policy makers and healthcare providers to deliver effective approaches in order to improve prevention practices of vaginitis among women in multi-ethnic communities. This study has identified points of interest which need to be put in attention for women’s health section which has been overlooked in Malaysia.